Institutional logics matter when coordinating resource integration - Edvardsson, Bo; Kleinaltenkamp, Michael; Tronvoll, Bård; McHugh, Patricia; Windahl, Charlotta (Marketing theory, 2014)
Resource integration has become an important concept in marketing literature. However, little is known about the systemic nature of resource integration and the ways the activities of resource integrators are coordinated and adjusted to each other. Therefore, we claim that institutions are the coordinating link that have impact on value cocreation efforts and are the reference base for customers’ value assessment. When conceptualizing the systemic nature of resource integration, we include the regulative, normative, and cognitive institutions and institutional logics. This article provides a framework and a structure for identifying and analyzing the influence of institutional logics on resource integration in service systems.